Fedorenko finite superelement method as special galerkin approximation - Galanin, M.; Savenkov, E. (Mathematical Modelling and Analysis, 2002)
In this work we introduce variational equation which natural Petrov‐Galerkin approximation leads to Fedorenko Finite Superelement Method (FSEM). FSEM is considered as Petrov‐Galerkin approximation of the certain problem for traces of boundary‐value problem solution at the boundaries of some subdomains (superelements). Iterative methods of solution of the same problem are well known domain decomposition methods. Some numerical results are presented. Fedorenko baigtinių elementų metodas kaip Galerkino metodo aproksimacija Santrauka. Pateikta vienos variacinės lygties Petrovo‐Galerkino aproksimacija, kuri veda į Fedorenko baigtinių elementų metodą. Jis nagrinėjamas kaip tam tikro uždavinio Petrovo‐Galerkino aproksimacija kraštinių uždavinių sprendinių pėdsakams kai kurių sričių (superelementų) kraštuose. Tokių uždavinių iteraciniai sprendimo metodai yra gerai žinomi kaip srities dekompozicijos metodai. Pateikti skaitinių eksperimentų rezultatai. First Published Online: 14 Oct 2010